A review on Nepalese Himalayan Buddhism - Dhakal, Devraj (Research Nepal Journal of Development Studies, 2024)
Nepalese Himalayan Buddhism represents a distinctive cultural, spiritual, and philosophical tradition shaped by centuries of trans-Himalayan exchange between Tibet, India, and indigenous Himalayan communities. This review synthesizes the existing scholarship on the origin, evolution, and cultural specificities of Himalayan Buddhism in Nepal, with particular focus on the practices of the Sherpa, Tamang, Gurung, and Yolmo communities. It further examines the doctrinal influences of the Vajrayāna and Mahāyāna schools, the role of monasteries (gompas), ritual traditions, art and architecture, pilgrimage culture, and contemporary challenges. Current literature suggests that Himalayan Buddhism in Nepal is a living heritage that continues to evolve amid modernization, tourism, and global spiritual trends. The review concludes by identifying research gaps and recommending areas for future ethnographic and interdisciplinary studies.